Synergistic Antiproliferative Effects of Chondroitin Sulfate and Fucoidan in Tumor-derived Spheroids: Insights From a 3D Cell Culture Approach - Nováková E; Zima J; Špaglová M; Labudová M; Šupolíková M (European Pharmaceutical Journal)
The aim of the study was to investigate the effects of chondroitin sulfate (CS) and fucoidan (F), as well as their combination (CS + F) on the growth and viability of spheroids derived from the non-tumor cell line NIH3T3 and the tumor cell line Hepa1c1c7 using a three-dimensional (3D) cell culture model. Spheroids were formed using the liquid overlay method and treated with different concentrations of substances. Flow cytometry was used to quantitatively assess the representation of live, apoptotic, necrotic, and dead cells in the spheroids after treatment. Spheroids from the non-tumor cell line NIH3T3 after treatment with CS and fucoidan were nontoxic to the cells. By light microscopy, we observed a significant proliferative effect in the case of CS and combination of fucoidan and CS (F + CS). On the contrary, in spheroids from the Hepa1c1c7 tumor cell line, after treatment with our compounds, the compounds, especially fucoidan and a combination of CS and fucoidan, showed antiproliferative effects, which confirms their synergistic antiproliferative effect. According to flow cytometry in non-tumor NIH3T3 spheroids, CS had the most significant effect on the proportion of viable cells, which confirmed its proliferative effect (66.43 ± 4.43%). In spheroids derived from the Hepa1c1c7 tumor cell line, flow cytometry revealed the highest number of dead cells in spheroids after treatment with a combination of CS and fucoidan (19.84 ± 5.80%). Based on our results, we can conclude that a combination of CS and fucoidan showed a synergistic antiproliferative effect on Hepa1c1c7 cell cultures. The 3D cell cultures provide a more physiologically relevant platform for drug testing, highlighting the importance of understanding cell–extracellular matrix interactions in cancer research.